2002
DOI: 10.1016/s0014-5793(02)02973-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced premature senescence in BJ and hTERT‐BJ1 human foreskin fibroblasts

Abstract: To test the involvement of the telomeres in the senescent phenotype, we used telomerase-immortalized human foreskin ¢broblasts (hTERT-BJ1). We exposed hTERT-BJ1 and parental BJ cells to either UVB or H 2 O 2 subcytotoxic stress(-es). Both cell lines developed biomarkers of replicative senescence: loss of replicative potential, increase in senescence-associated L L-galactosidase activity, typical senescence-like morphology, overexpression of p21 WAFÀ1 and p16 INKÀ4a , and decreased level of the hyperphosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
62
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 24 publications
15
62
0
1
Order By: Relevance
“…This is consistent with data reported previously, albeit on cells with fewer PD (Jiang et al 1999, Vaziri et al 1999, Gorbunova et al 2002. Furthermore, cell cycle checkpoint activation after other forms of DNA damage were unaffected by hTERT-mediated immortalization (Gorbunova et al 2002, De Magalhaes et al 2002. These combined data suggest that fibroblast immortalization by telomerase activation alone does not affect the response of cells to DNA damage in terms of cellular sensitivity and cell cycle response.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with data reported previously, albeit on cells with fewer PD (Jiang et al 1999, Vaziri et al 1999, Gorbunova et al 2002. Furthermore, cell cycle checkpoint activation after other forms of DNA damage were unaffected by hTERT-mediated immortalization (Gorbunova et al 2002, De Magalhaes et al 2002. These combined data suggest that fibroblast immortalization by telomerase activation alone does not affect the response of cells to DNA damage in terms of cellular sensitivity and cell cycle response.…”
Section: Discussionsupporting
confidence: 91%
“…So, although hTERT lengthened the mean telomeric length in the fibroblasts and prevented replicative senescence during normal cell culturing (chronic stress), it did not prevent DNA damage (acute stress)-induced entry into senescence. This suggests that senescence due to end-replication problems might-at least in part-occur via separate pathways than senescence induced by DNA damage, which is in agreement with earlier observations using both ionizing radiation and/or other forms of DNA damage-inducing stresses like H 2 O 2 or UV-B (Chen et al 2001, Gorbunova et al 2002, De Magalhaes et al 2002, Matuoka and Chen 2002. It is also consistent with recent findings by te Poele et al (2002), who showed that DNA damage can induce senescence in tumour cells provided they express wild-type p53 and p21 WAF-1,CIP-1 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, p16 can be easily detected in cultured human and mouse mesenchymal and epithelial cells, where its expression is associated with an irreversible growth arrest status (Voorhoeve and Agami, 2003). It has been repeatedly reported that p16 expression can be induced in vitro by different forms of cell stress (Chazal et al, 2002;de Magalhaes et al, 2002;Chen et al, 2004). These and other observations suggest that p16 is a checkpoint protein that does not participate in the control of normal cell proliferation, and whose expression is triggered only in some particular circumstances such as cell stress, cell senescence or the activation of certain oncogenes (Roussel, 1999;Lowe and Sherr, 2003).…”
mentioning
confidence: 99%
“…It has been reported that p16 expression can be induced by oxidative stress in cultured adherent human cells (de Magalhaes et al, 2002;Chen et al, 2004). DNA damage triggered by different agents such as UV light and chemicals can also induce p16 expression (Chazal et al, 2002), whereas p16 inactivation has been reported in gamma irradiation-induced thymic lymphomas (Malumbres et al, 1997).…”
mentioning
confidence: 99%